Re-Design Interior Gereja Katolik Santo Paulus Di Surabaya Berdasarkan Ajaran Allah Tritunggal - Tantu, Frederick Irianto (Intra, 2014)
St. Paul Catholic Church is one of the Catholic Churches in Surabaya. This church located on the complex of Navy Juanda, on Juanda-Waru street. Trinity is one of the main doctrine in Catholic : the God in three persons : Father, Son, and Holy Spirit. In this design work, writer makes a new interior design for this church which supposed to give an illustration about Catholicâ doctrine : The Trinity. The interior that based on doctrine means that the design will reflect the presents of God Trinity, direct or indirect - through the churchâs interior. So this design can introducing the Catholic doctrine to society, specially to give comprehension for the Catholic people.